Successful management of severe allergic reactions to platelet transfusion with omalizumab: A case report. Issue 44 (5th November 2021) - Choi, Yeonjoo; Byun, Ja Min; Kim, Inho; Park, Jin Hyun; Kim, Ki Hwan; Kim, Jin-Soo; Choi, In Sil; Yang, Min-Suk; Park, Hyunkyung
Abstract: Rationale: An allergic transfusion reaction is a common side effect of transfusions of red blood cells. Using washed red blood cells is the most effective method for preventing such a reaction. However, the availability of other washed transfusion components, including platelets, is limited. Patient concerns: A 69-year-old patient with acute myeloid leukemia progressed from myelodysplastic syndrome and was treated with azacitidine. She experienced a minor reaction to platelet transfusion that initially responded to the administration of corticosteroids and antihistamines. However, she worsened even after subsequent preventive treatments and was referred to the emergency department due to anaphylaxis. The patient developed hypotension, chest pain, and dyspnea 10 minutes after the initiation of platelet transfusion. Diagnoses: She was diagnosed with platelet-induced anaphylaxis. Interventions: In an attempt to prevent anaphylaxis, 150 mg of omalizumab was prescribed 1 week prior to transfusion. However, she experienced anaphylaxis again and was administered intramuscular epinephrine. For the following transfusion, we treated her with a 300 mg dose of omalizumab 24 hours before the transfusion. Outcomes: She tolerated well and continued to receive further chemotherapy and platelet transfusion with premedication. Lessons: This case suggests that omalizumab is a good candidate for the management of severe allergic transfusion reactions.